Role of montelukast in asthma treatment in 2025 - Pawliczak, Rafał (Alergologia Polska - Polish Journal of Allergology, 2025)
This review paper explores the role and significance of antileukotriene therapy in asthma management. It highlights the involvement of the arachidonic acid metabolite-dependent pathway, regardless of the formal phenotype and, in some cases, the endotype of asthma. The paper identifies scenarios where antileukotriene therapy serves as a valuable adjunct to existing treatments, regardless of disease severity. In addition, it examines the adverse effects of montelukast, with particular focus on unproven neuropsychiatric concerns. Overall, montelukast remains a safe and effective option in asthma treatment.